Obsidian Reflections : Symbolic Dimensions of Obsidian in Mesoamerica - Levine, Marc N.; Carballo, David M. (Book collections on Project MUSE., 2014)
"Departing from the political economy perspective taken by the vast majority of volumes devoted to Mesoamerican obsidian, Obsidian Reflections is an examination of obsidian's sociocultural dimensions--particularly in regard to Mesoamerican world view, religion, and belief systems. Exploring the materiality rather than only the functionality of this volcanic glass, this book considers the interplay between people, obsidian, and meaning and how these relationships shaped patterns of procurement, exchange, and use. An international group of scholars, hailing from Belize, France, Japan, Mexico, and the United States provide a variety of case studies from Mexico, Guatemala, Belize, and Honduras. The authors draw on archaeological, iconographic, ethnographic, and ethnohistoric data to examine obsidian as a touchstone for cultural meaning, including references to sacrificial precepts, powerful deities, landscape, warfare, social relations, and fertility. In addition, Obsidian Reflections underscores the necessity of understanding obsidian from within its cultural context--from the perspective of the indigenous people of Mesoamerica. It will be of great interest to Mesomaericanists as well as students and scholars of lithic studies and material culture."--